KONSEP HUKUM DALAM PELAKSANAAN PERJANJIAN PEMBIAYAAN KONSUMEN PADA PT. MEGA FINANCE CABANG PALU - Nafri, Moh. (Katalogis, 2015)
The problem was legal concept in implementing an agreement of consumer’s funding. This research aimed at finding out the existing legal concept in implementing an agreement of consumer’s funding. This research used empirical legal method by using primary legal materials and secondary ones which were then presented inductively. This means from specific things to general ones. The research shows that the existing legal concept in implementing the agreement of consumer’s funding at PT Mega Finance of Palu is the concept of rights and responsibility of each party has been more specific compared with the legal constract. The legal concept of rights and responsibility does not provide an equal position of all the parties. Justice implemented in consumers’ finding agreement is not relatively the same as the one in John Rawls used so far. The attitude by the business actors who has not provided an equal position to the cunsumers has been in contrast with the justice intending an equal freedom for anyone.